2007
DOI: 10.1029/2006ja011938
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal evolution of radio wave pump‐induced ionospheric phenomena near the fourth electron gyroharmonic

Abstract: [1] On 12 November 2001, the European Incoherent Scatter (EISCAT) high-frequency (HF) radio wave transmitter facility, operating in O-mode at 5.423 MHz with 550 MW effective radiated power, produced artificial optical rings which appeared immediately at transmitter turn-on and collapsed into blobs after $60 s while descending in altitude. A similar descent in altitude was observed in the EISCAT ultra high frequency (UHF) ion line enhancements. Likewise, the stimulated electromagnetic emission (SEE) spectra cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 77 publications
7
39
0
Order By: Relevance
“…Gurevich et al (2001Gurevich et al ( , 2002 proposed a magnetic zenith mechanism for making a large fraction of the ERP available in the plasma production region, and means for the electron acceleration. Bernhardt et al (1989), Djuth et al (1999) Pedersen et al (2003, Gustavsson et al (2005), Holma et al (2006), Ashrafi et al (2007) have also worked on electron acceleration mechanisms and experimental evidence for their presence. Our work here shows the signatures of the magnetic zenith mechanism in terms of both rapid formation of striations and strong Langmuir turbulence when the plasma-density enhancements were produced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gurevich et al (2001Gurevich et al ( , 2002 proposed a magnetic zenith mechanism for making a large fraction of the ERP available in the plasma production region, and means for the electron acceleration. Bernhardt et al (1989), Djuth et al (1999) Pedersen et al (2003, Gustavsson et al (2005), Holma et al (2006), Ashrafi et al (2007) have also worked on electron acceleration mechanisms and experimental evidence for their presence. Our work here shows the signatures of the magnetic zenith mechanism in terms of both rapid formation of striations and strong Langmuir turbulence when the plasma-density enhancements were produced.…”
Section: Discussionmentioning
confidence: 99%
“…We should acknowledge that invoking the above explanations need not exclude other electron acceleration processes from occurring as well. For example, Ashrafi et al (2007) suggested that upper hybrid waves, which propagate perpendicular to the magnetic field, and Langmuir waves, which propagate parallel to the magnetic field, act simultaneously to accelerate electrons even in the steady state. However the role of Langmuir turbulence near the reflection height in electron acceleration remains central.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, many experimental studies have been applied to the large-scale F-region modification by powerful HF radio waves and many interesting results were obtained (Utlaut and Violette, 1974;Gordon and Carlson, 1974;Mantas et al, 1981;Jones et al, 1986;Djuth et al, 1987;Duncan et al, 1988;Hansen et al, 1992;Mantas, 1994;Honary et al, 1995;Robinson et al, 1996;Frolov et al, 1997;Gustavsson et al, 2001;Rietveld et al, 2003;Ashrafi et al, 2007;Clausen et al, 2008;Pedersen et al, 2008). It turns out that significant variations in the electron temperatures and densities can be produced by powerful HF waves in the F-layer.…”
Section: Introductionmentioning
confidence: 98%
“…It is doubtful that the EAP value of 100 MW is attainable for the existing high-power radio wave heaters, in particular for the "Sura" heating facility (Nizhny Novgorod, Russia) whose effective radiated power (ERP) varies between 150 and 280 MW (Belikovich et al, 1999). Nevertheless, it is not impossible that the EAP value of 100 MW may be acquired in the future with the help of some mid-latitude ionospheric heater.…”
Section: Effects Of Heating In the Dark Ionospherementioning
confidence: 99%